2011
DOI: 10.1080/14616734.2011.584405
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to earned-security: The role of alternative support figures

Abstract: This study explored the kinds of relationship experiences associated with earned-security, i.e., the extent to which mothers who report early negative relationship histories with their parents are later able to form a secure working model of attachment (indicated by the ability to speak clearly and coherently about these histories). Mothers from a low-risk sample (N = 121) expecting their first child completed the Adult Attachment Interview (AAI), which was used to assess earned-security retrospectively using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 15 publications
5
57
0
5
Order By: Relevance
“…For instance, Pearson and colleagues (1994) reported that adults with an earned secure classification demonstrated parenting styles that were comparable to those of adults in the continuous secure group-with both groups demonstrating significantly higher parental warmth and structure than an insecure comparison group. Similar findings were reported by Saunders, Jacobvitz, Zaccagnino, Beverung, and Hazen (2011), who found that both earned secure and continuous secure mothers were equally likely to have a securely attached infant (see also Phelps, Belsky, & Crnic, 1998). Furthermore, the marital functioning of individuals with an earned secure classification has been found to be no different from that of individuals with a continuous secure classification (Paley, Cox, Burchinal, & Payne, 1999).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…For instance, Pearson and colleagues (1994) reported that adults with an earned secure classification demonstrated parenting styles that were comparable to those of adults in the continuous secure group-with both groups demonstrating significantly higher parental warmth and structure than an insecure comparison group. Similar findings were reported by Saunders, Jacobvitz, Zaccagnino, Beverung, and Hazen (2011), who found that both earned secure and continuous secure mothers were equally likely to have a securely attached infant (see also Phelps, Belsky, & Crnic, 1998). Furthermore, the marital functioning of individuals with an earned secure classification has been found to be no different from that of individuals with a continuous secure classification (Paley, Cox, Burchinal, & Payne, 1999).…”
supporting
confidence: 78%
“…This hypothesis is supported by higher rates of internalizing distress among earned secure adults (Pearson et al, 1994;Roisman et al, 2002) and, even more compellingly, by an experimental manipulation in which a sad mood induction prior to the AAI was linked to higher likelihood of an earned secure classification (Roisman et al, 2006). Indeed, studies attempting to address other empirical questions regarding earned security now routinely control for internalizing symptoms (e.g., Saunders et al, 2011) due to the strength of this finding.…”
Section: Bulletin Of the Menninger Clinicmentioning
confidence: 66%
See 1 more Smart Citation
“…Fortunately, the opportunity to achieve a secure attachment status remains available across the lifespan (Saunders, Jacobvitz, Zaccagnino, Beverung, & Hazen, 2011). Earned secure attachment refers to the achievement of a secure attachment status later in life when it was not achieved through the first family relationships.…”
Section: Restoring the Promisementioning
confidence: 99%
“…The concept of "earned-security" is also relevant to an understanding of such clients. Pearson, Cohn, Cowan, and Cowan (1994) found that a significant proportion of individuals with negative attachment experiences in childhood were nevertheless able to exhibit secure attachment patterns in adult life, on the basis of involvement of alternative support figures (Saunders, et al, 2011). Clearly, a relationship with a psychotherapist represents a potentially curative form of support.…”
Section: Guiding Conceptionmentioning
confidence: 99%